2011
DOI: 10.1097/hjh.0b013e32834c625c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of valsartan compared to enalapril in hypertensive children

Abstract: Valsartan and enalapril provided comparable BP reductions and effective BP control and were well tolerated in hypertensive children aged 6-17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 34 publications
3
60
0
4
Order By: Relevance
“…One exception is a study comparing valsartan with enalapril, which showed similar efficacy and adverse event rates for these two agents (211). Clinicians who care for children and young adults with HTN need to be familiar with at least one drug from each class of agent.…”
Section: Monotherapymentioning
confidence: 99%
“…One exception is a study comparing valsartan with enalapril, which showed similar efficacy and adverse event rates for these two agents (211). Clinicians who care for children and young adults with HTN need to be familiar with at least one drug from each class of agent.…”
Section: Monotherapymentioning
confidence: 99%
“…This ARB has also demonstrated efficacy and safety in doses ranging from 10 to 160 mg in children aged 6-16 years [18]. In another active-controlled study in hypertensive children aged 6-17 years, valsartan provided BP reductions comparable or superior to enalapril and was well tolerated [19]. Valsartan is now approved in the United States and the European Union in children aged 6 years or older [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Only the lisinopril RCT used DBP as their primary outcome variable 15. Most of the studies determined BP auscultatory, 24 hours ambulatory blood pressure measurement (ABPM) was used in four studies 18 21 22 24 25…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of enalapril has been studied in two large double-blind RCTs, evaluating 110 and 281 hypertensive children, respectively 17 18. Wells et al 17 found a linear dose–response ratio, more specifically a decrease of 0.3 mm Hg in DBP per unit increase in dose ratio, and a significant mean difference in DBP of 6.1±2 mm Hg between the three groups of enalapril compared with placebo.…”
Section: Resultsmentioning
confidence: 99%